2005
DOI: 10.1007/s10532-004-6593-x
|View full text |Cite
|
Sign up to set email alerts
|

Fate and biodegradability of sulfonated aromatic amines

Abstract: Ten sulfonated aromatic amines were tested for their aerobic and anaerobic biodegradability and toxicity potential in a variety of environmental inocula. Of all the compounds tested, only two aminobenzenesulfonic acid (ABS) isomers, 2-and 4-ABS, were degraded. The observed degradation occurred only under aerobic conditions with inocula sources that were historically polluted with sulfonated aromatic amines. Bioreactor experiments, with non-sterile synthetic wastewater, confirmed the results from the aerobic ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(55 citation statements)
references
References 35 publications
1
51
0
3
Order By: Relevance
“…On the other hand, most of the benzene-based aromatic amines are completely removed. Tan et al (2005) studied the fate and biodegradability of benzene-based and naphthalene-based sulphonated aromatic amines in a bioreactor. The authors reported that simple, benzene-based sulphonated amines, such as monoamino benzene sulphonic acid, were completely mineralized while diamino benzene sulphonic acid and other sulphonated amines containing naphthalene were resistant to aerobic biodegradation.…”
Section: Toxicity At Various Stages Of Anaerobic-aerobic Biodegradationmentioning
confidence: 99%
“…On the other hand, most of the benzene-based aromatic amines are completely removed. Tan et al (2005) studied the fate and biodegradability of benzene-based and naphthalene-based sulphonated aromatic amines in a bioreactor. The authors reported that simple, benzene-based sulphonated amines, such as monoamino benzene sulphonic acid, were completely mineralized while diamino benzene sulphonic acid and other sulphonated amines containing naphthalene were resistant to aerobic biodegradation.…”
Section: Toxicity At Various Stages Of Anaerobic-aerobic Biodegradationmentioning
confidence: 99%
“…Les amines aromatiques formées lors de la première étape de la biodégradation (azoréduction) s'accumulent dans le milieu extracellulaire et résistent à la bio-oxydation. La dégradation des amines aromatiques, en particulier celle des amines sulfoniques, est limitée, voire inhibée par leur faible transfert à travers la membrane cellulaire (TAN et al, 2005).…”
Section: Décoloration Par Les Bactériesunclassified
“…Des amines aromatiques sulfoniques, connues comme étant très résistantes à l'attaque bactérienne à cause de leur faible transfert à travers la membrane cellulaire (FEIGEL et kNACkMUSS, 1993;TAN et al, 2005), ont été facilement biodégradables par des bactéries de genre Pseudomonas (Figure 6). …”
Section: Décoloration Par Les Bactériesunclassified
“…However, other studies also reported that oxygen stimulated bacterial growth or helped in the expansion of substrate utilization range, and consequently enhanced the current generation capability in MFCs (Biffinger et al, 2009;Rosenbaum et al, 2010). In case of aromatic amine, their degradation is much more flexible and more efficient under aerobic condition than anaerobic condition (Kahng et al, 2000;Tan et al, 2005). Several pure or mixed bacterial cultures use various aromatic amines as sole carbon and energy sources (Chen et al, 2012;Juarez-Ramirez et al, 2012;Sheludehenko et al, 2005).…”
Section: Introductionmentioning
confidence: 99%